2013
DOI: 10.1371/journal.pone.0064570
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Is a Key Target in Multiple Essential Tumor Functions of Prostate Cancer: Uptake of Radiolabeled Acetate as a Predictor of the Targeted Therapy Outcome

Abstract: Fatty acid synthase (FASN) expression is elevated in several cancers, and this over-expression is associated with poor prognosis. Inhibitors of FASN, such as orlistat, reportedly show antitumor effects against cancers that over-express FASN, making FASN a promising therapeutic target. However, large variations in FASN expression levels in individual tumors have been observed, and methods to predict FASN-targeted therapy outcome before treatment are required to avoid unnecessary treatment. In addition, how FASN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 45 publications
3
72
1
1
Order By: Relevance
“…Previous studies have demonstrated that the upregulation of FASN increases tumor cell proliferation (25), decreases the rate of apoptosis (17), and increases the resistance to chemotherapy and radiation of tumor cells in various human neoplasms (26). In line with this, the present study revealed that downregulation of FASN caused a significant reduction in the proliferation of A549 cells, suggesting that FASN may be involved in NSCLC oncogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated that the upregulation of FASN increases tumor cell proliferation (25), decreases the rate of apoptosis (17), and increases the resistance to chemotherapy and radiation of tumor cells in various human neoplasms (26). In line with this, the present study revealed that downregulation of FASN caused a significant reduction in the proliferation of A549 cells, suggesting that FASN may be involved in NSCLC oncogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…The biologic mechanisms that link FASN activity with metastatic spread are largely unknown and it is possible to speculate that the decreased number of metastatic lymph nodes here observed with orlistat is consequence of the cell growth/migration inhibition and enhanced apoptosis. It was also recently shown that the inhibition of lipogenesis reduces invadopodia formation and gelatinolytic activity of Src-transformed 3T3 cells (47) and that orlistat prevents pseudopodia formation and inhibits human prostate cancer cell migration and invasion (48). Kuemmerle and colleagues (49) recently demonstrated that in addition to de novo lipogenesis, cancer cells can use the lipoprotein lipase (LPL) and CD36 to acquire fatty acids from the circulation by lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Orlistat, a selective inhibitor of FAS, was tested for target inhibition in murine prostate cancer models. The degree of target expression as determined with 11 C-acetate imaging correlated with response to FAS inhibition (55).…”
Section: C-acetate As a Predictive Prognostic And Intermediate Endpmentioning
confidence: 99%
“…Predictive biomarkers are designed to determine whether a specific therapeutic target is expressed (Fig. 5) (55). FAS is overexpressed in prostate and other cancers and has been explored as a potential therapeutic target.…”
Section: C-acetate As a Predictive Prognostic And Intermediate Endpmentioning
confidence: 99%